Answer :


Using the splitting middle term - the middle term of the general equation is divided in two such values that:


Product = a.c


For the given equation a = √(3;) b = 11; c = 6√3


= √3.6√3 = 3.6 = 18


(using 3 = √3.√3


And either of their sum or difference = b


= 11


Thus the two terms are 9 and 2


Sum = 9 + 2 = 11


Product = 9.2 = 18




√3 x(x + 3√3) + 2(x + 3√3) = 0


(using 9 = 3.3 = 3√3 √3)


(√3 x + 2)(x + 3√3) = 0


(√3 x + 2)(x + 3√3) = 0



Roots of equation are


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Which of the follRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics